Essentials of modern spectrum management - Cave, Martin (The Cambridge wireless essentials series, 2007)
Are you fully up-to-speed on today's modern spectrum management tools? As regulators move away from traditional spectrum management methods, introduce spectrum trading and consider opening up more spectrum to commons, do you understand the implications of these developments for your own networks? This 2007 book was the first to describe and evaluate modern spectrum management tools. Expert authors offer insights into the technical, economic and management issues involved. Auctions, administrative pricing, trading, property rights and spectrum commons are all explained. A series of real-world case studies from around the world is used to highlight the strengths and weaknesses of the various approaches adopted by different regulators, and valuable lessons are drawn from these. This concise and authoritative resource is a must-have for telecom regulators, network planners, designers and technical managers at mobile and fixed operators and broadcasters, and academics involved in the technology and economics of radio spectrum.